Payoff shares in two-player contests - Samuel Häfner; Georg Nöldeke (Games, 2016)
In imperfectly discriminating contests with symmetric valuations, equilibrium payoffs are positive shares of the value of the prize. In contrast to a bargaining situation, players' shares sum to less than one because a residual share of the value is lost due to rent dissipation. In this paper, we consider contests with two players and investigate the relationship between these equilibrium shares and the parameters of a class of asymmetric Tullock contest success functions. Our main finding is that any players' shares that sum up to less than one can arise as the unique outcome of a pure-strategy Nash equilibrium for appropriate parameters.
Keywords: C72; D72; D74; 330; contests; pure-strategy equilibrium; rent-dissipation